O sposobach i problemach reprezentacji wiedzy w nauce o zarządzaniu wiedzą - Zeidler, Paweł (Wydawnictwo Naukowe UAM, 2014)
The paper presents a preliminary analysis of methodological issues relating to the representation of knowledge that is managed in an organization. The problem of adequate ways of representing that knowledge and the concept of knowledge representation itself are analyzed. Particular attention is paid to the issue of the representation of tacit knowledge which plays an extremely important role in an organization and gives it a competitive advantage. The analyses are carried out based on the assumption that models are the most convenient way of representing knowledge and are used to solve problematic situations that arise in the course of an organization’s activity.
Methods and Problems of Knowledge Representation in the Science of Knowledge Management
Keywords: knowledge management; propositional knowledge; procedural knowledge; knowledge representation; solving-problem activity